The Satisfaction of Users Comparing the Transportation Services Between J&T Express and Flash Express - สุขประเสริฐ, ณฐพงศ์; ฐานะชาลา, ธารกมล; โพธิ์เกษม, ภนิดา; กาวิชา, ศิริวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study focuses on examining the satisfaction of users by comparing the transportation services between J&T EXPRESS and FLASH EXPRESS. The research employs a quantitative approach with a purposive sampling method, selecting a sample of 829 participants. A questionnaire was used to collect data on demographic characteristics such as gender, age, occupation, and education level. The results indicated that most respondents were female, aged between 20-29 years.           The findings reveal that J&T Express offers lower service fees compared to its competitors, with services such as home pick-up and promotional discounts, leading to higher user satisfaction. On the other hand, Flash Express provides a variety of services, including standard and express parcel delivery, with reasonable service fees. Additionally, Flash Express offers cash-on-delivery services and multiple payment methods, such as credit cards and bank transfers, which contribute to users' satisfaction with the service.